Case Report: Recurrent intraocular pressure elevation during hemodialysis in a patient with pseudoexfoliation glaucoma - Herman, Joshua Eli; Kanda, Pushpinder; Akbari, Ayub; Kundapur, Deeksha; Podury, Soumya; Jegatheswaran, Januvi (Frontiers in Ophthalmology, 2025)
IntroductionIntraocular pressure (IOP) elevation during dialysis has been observed in patients with glaucoma. This is thought to result from rapid shifts in plasma osmolality, leading to fluid movement into the anterior chamber, a phenomenon referred to as ocular dialysis disequilibrium. This case highlights a patient with advanced pseudoexfoliation glaucoma who developed recurrent, symptomatic IOP spikes during dialysis, posing management challenges.MethodsCase report.ResultsA 65-year-old male with advanced pseudoexfoliation glaucoma experienced recurrent left eye pain and vision loss during hemodialysis, with IOP spikes up to mid 50s (mmHg), requiring early dialysis termination. Medical management including topical drops, oral acetazolamide, and dialysis modifications failed to adequately control IOP. The patient later underwent Ahmed glaucoma valve implantation which stabilized IOP (8–13 mmHg), eliminated dialysis-related pain, and allowed return to standard dialysis sessions. At 6 months, visual acuity was 20/80 + 2 OS with IOP well controlled on topical therapy.ConclusionThis case demonstrates that ocular dialysis disequilibrium can cause symptomatic IOP spikes in glaucoma patients and may be unresponsive to medical therapy alone. Surgical intervention may be necessary for long-term IOP control. Early recognition and interdisciplinary coordination between ophthalmology and nephrology is critical to prevent irreversible vision loss.